Unmanned aerial vehicle systems in crop production : a compendium - Krishna, K. R. (Kowligi R.) (Oakville, ON ; Palm Bay, Florida : Apple Academic Press Inc., 2020)
"This volume provides a useful detailed review of 250 UAVs that examines their usefulness in enhancing profitability, yield, and quality of crop production. A detailed view of the recent trends indicates an increase in agricultural drone production. Millions of dollars have been invested in start-ups that produce agro-drones in past several years. North America, Europe, China and the Far East have excelled in offering a large number of UAV models. Some of them are versatile, a few are specific, and many of them are low cost. With so many drone models (over 1200) available, how do farmers and agricultural specialist choose the models best for them? This compendium examines the most useful drones and provides the pertinent details about each drone, its producer, cost incurred, and its pros and cons. It covers their technical specifications, suitability for various purposes, previous performances in farms, and possible benefits to farmers. The introduction sets the scene, emphasizing the need for this compendium and expounding on the benefits of UAVs in crop production. The volume describes the agricultural uses of UAVs and provides a status report of the drone usage in farms. Drones can be used to measure soil fertility and monitor crops, to time the spraying of liquid fertilizers and plant protection chemicals to control pests and diseases, to monitor irrigation, to map yields, and to make forecasts. The volume goes into great detail about the specifications of each of 250 agricultural drone models covered. These include fixed-wing drones, fixed-wing (hybrid) VTOL helicopters, multi-copters, tilted-wing drones, etc. The book includes a few drones meant more for military or other purposes (e.g. recreation/fun) but that could be easily modified and adapted for the farming sector. A detailed listing of agricultural and nonagricultural uses of each drone model is made available. The reviews compare activities among the UAVs, such aerial imagery of crops, ability to provide spectral analyses to collect useful data about a crop's growth patterns, and how they can be used to gauge crop canopy temperature (i.e. water stress index), determine grain maturity, and much more. The volume also includes addresses and useful information about industries that produce drones have also been included. One chapter deals exclusively with blimps, balloons and kites that could also be used for aerial survey of crops. This timely book is just in time to address the burgeoning aerial robot industry worldwide. This compendium will be valuable for farmers, agricultural engineers, agricultural research centers, universities, and faculty and students worldwide. Agricultural companies and those in aeronautics technology will also find much of value in this reference."--
Introduction to unmanned aerial vehicle systems utilized in agriculture -- Fixed-winged unmanned aerial vehicle systems utilized in agriculture -- Helicopter and multirotor unmanned aerial vehicle systems utilized in agriculture -- Parachutes, blimps, balloons, and kites as unmanned aerial vehicles useful in agriculture -- Sensors and image-processing computer software relevant to unmanned aerial vehicle-based technology in agriculture -- Applications of unmanned aerial vehicle systems in agriculture: a few examples.
OCLC-licensed vendor bibliographic record.
Keywords: Agriculture -- Remote sensing; Drone aircraft; Crops; SCIENCE / General; TECHNOLOGY / Aeronautics & Astronautics; TECHNOLOGY / Agriculture / Crop Science